Prolonged exposure therapy for adolescents with PTSD : emotional processing of traumatic experiences : therapist guide - Foa, Edna B. (Treatments that work., 2009)
"This program is specifically intended for adolescents suffering from posttraumatic stress disorder. Clients are exposed to safe but anxiety-provoking situations as a way of overcoming their trauma-related fears. Recounting the memory of the trauma also helps clients emotionally process their traumatic experiences in order to diminish PTSD symptoms. The workbook is designed for adolescent use and includes teen-friendly forms to reinforce the skills learned in therapy"--Provided by publisher